1977
DOI: 10.1016/s0022-5347(17)57972-0
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the Existence of Canine Prostatic Lymphatics by Radioisotope Techniques

Abstract: Radioactive 198Au colloid injected into the canine prostate through an opened bladder to avoid violating the prostatic capsule was observed to migrate from the prostate to the regional lymph nodes. Significant isotope uptake in the kidney, liver, rectus muscle and distant lymph nodes was not detected, thus indicating direct spread of the isotope to the regional lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Zunächst wurde dabei angenommen, dass die fehlende Darstellung von Lymphknoten für das Vorhandensein von Lymphknotenmetastasen spricht. Menon et al [23] konnten erstmals die bis dahin umstrittene Existenz von intraprostatischen Lymphbahnen mittels szintigraphischer Studien an Hunden zeigen, bei welchen der Tracer über einen transvesikalen Zugang intraprostatisch injiziert wurde. Diese Ergebnisse wurden von Kaplan et al bestätigt [24], wobei erstmals eine transrektale intraprostatische Injektion mit anschließend erfolgreicher Lymphszintigraphie durchgeführt wurde.…”
Section: Sentinel-konzept Beim Prostatakarzinomunclassified
“…Zunächst wurde dabei angenommen, dass die fehlende Darstellung von Lymphknoten für das Vorhandensein von Lymphknotenmetastasen spricht. Menon et al [23] konnten erstmals die bis dahin umstrittene Existenz von intraprostatischen Lymphbahnen mittels szintigraphischer Studien an Hunden zeigen, bei welchen der Tracer über einen transvesikalen Zugang intraprostatisch injiziert wurde. Diese Ergebnisse wurden von Kaplan et al bestätigt [24], wobei erstmals eine transrektale intraprostatische Injektion mit anschließend erfolgreicher Lymphszintigraphie durchgeführt wurde.…”
Section: Sentinel-konzept Beim Prostatakarzinomunclassified
“…Lymphatic drainage of the prostate gland in experimental animals such as the canine has not been reported until now. Menon et al [13] injected 1 9 8 A~ into the prostate gland to identify the prostatic lymph nodes, but did not demonstrate its lymphatic drainage. The present study revealed 3 directions of lymphatic drainage in the prostate gland, the external iliac, internal iliac, and posterior types, although the localization of the internal iliac and presacral lymph nodes in the canine was different from that in the human.…”
Section: Connolly Et Al [I I] Investigated the Intraprostatic Lymphamentioning
confidence: 99%
“…There has been disagreement about the existence of lymphatics in the human prostatic parenchyma. Menon et al (1977) injected Ig8Au colloid into the dog prostate through an open bladder and showed the regional lymph nodes. Similarly, Shridhar (1979), using a range of techniques, demonstrated lymphatics in the prostate of dog and man.…”
mentioning
confidence: 99%